2019
DOI: 10.1002/jhet.3694
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of new pyrazoline‐thiazole derivatives as monoamine oxidase inhibitors

Abstract: A novel series of 1,3,5‐trisubstituted‐2‐pyrazoline derivatives (4a‐4k) was synthesized and their chemical structures characterized by 1H NMR, 13C NMR, and mass spectroscopy. These compounds were evaluated as inhibitors for of type A and type B monoamine oxidase (MAO) enzymes. The most common inhibitors of MAO enzymes used to treat depression and anxiety such as selegiline and moclobemide drugs were used as reference agents. A result of biological evaluation of these compounds revealed compounds 4c, 4d, and 4ı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…(Figure 18). Acar Çevik et al 71 The introduction of a methoxy group in these derivatives was observed to enhance inhibitory activity and selectivity for MAO A enzymes, which play a crucial role in the metabolism of neurotransmitters such as serotonin, norepinephrine, and dopamine in the central nervous system (Scheme 17).…”
Section: Pyrazole-linked Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Figure 18). Acar Çevik et al 71 The introduction of a methoxy group in these derivatives was observed to enhance inhibitory activity and selectivity for MAO A enzymes, which play a crucial role in the metabolism of neurotransmitters such as serotonin, norepinephrine, and dopamine in the central nervous system (Scheme 17).…”
Section: Pyrazole-linked Hybridsmentioning
confidence: 99%
“…Acar Çevik et al 71 have detailed the synthetic route for the preparation of 2-(3-(4-(4-benzylpiperidin-yl)phenyl)-5-phenyl-4,5-dihydro-1 H -pyrazol-1-yl)-4-(substitutedphenyl)-thiazole conjugates ( 45a – 45k ). This involved the utilization of phenacyl bromide 43 and 3-(4-(4-benzylpiperidin-1-yl)phenyl)-5-phenyl-4,5-dihydro-1 H -pyrazone-1-carbothioamides 44 through a refluxing reaction mixture on a water bath for a duration of 3 h in ethanol, resulting in moderate yields.…”
Section: Thiazolyl-pyrazoline Hybridsmentioning
confidence: 99%